Ultrasound elastography evaluation of breast masses with FNAC and/or histopathological correlation - Chhadi, Shyam; Chhadi, Tulsi; Bagde, Kamlesh (International Journal of Research in Medical Sciences, 2018)
Background: Breast cancer is the most frequently diagnosed cancer amongst women worldwide. Ultrasound elastography is a non-invasive method for determining tissue mechanical properties and seems to be compensating for the deficiencies of conventional USG. We aimed to evaluate the sensitivity and specificity of ultrasound elastography in detection and characterization of various breast masses and study its role in differentiating benign and malignant breast masses with FNAC and/or histopathological correlation. Methods: A total of 126 patients with breast lesions confirmed on USG were enrolled for the study, out of which 10 were lost to follow-up and excluded. Consecutive patients presenting with palpable breast lesions were assessed with conventional B-mode USG. Those confirmed to have breast lesion were then assessed with Strain Elastography (SE). FNAC was used for histopathological confirmation of malignant lesions. The benign lesions were diagnosed by a combination of FNAC and biopsy and were followed up for 6 months. Results: There were 56 (48.3%) malignant and 60 (51.7%) benign lesions. A sensitivity of 83.9% and a specificity of 91.7% was obtained for elasticity score when cut-off value of 3.5 was used (area under the curve- 0.924, 95% CI- 0.869 to 0.979, p-0.0001). Sensitivity of 91.1% and specificity of 88.3% was obtained for SR scores, when a cut off of 2.94 was used (area under the curve- 0.969, 95% CI- 0.943-0.995, p-0.0001). The Pearson correlation coefficient for elasticity scores and SR values was 0.936, indicating very good agreement (correlation) between the two methods. Conclusions: Ultrasound elastography is a simple and rapid method that can improve the sensitivity and specificity of USG and can decrease the rate of unnecessary biopsies.